ANALISIS BIAYA PROYEK DENGAN METODOLOGI SIX SIGMA DAN SIMULASI MONTE CARLO - Mirza, Ahmad Haidar; Setiawan, Herri (JURNAL ILMIAH MATRIK, 2012)
The use of structured methodologies is needed to accelerate the repair process, helping reduce costs and improve efficiency. Monte Carlo simulation and Six Sigma methodologies can be used to analyze the risks associated with the total cost of the project. Monte Carlo simulation is applied to understand the variability in total costs resulting from the probabilistic cost item. With the range of variation of the Six Sigma methodology of project costs can be reduced by operating on input factors with the greatest impact on total costs. In this paper we will discuss how Monte Carlo simulation can be used in Six Sigma methods to analyze project costs. The results obtained can identify the elements of the risk of high costs, the difference between the estimates of each cost component and the average cost is obtained. Keywords: Simulation, Monte Carlo, Six Sigma